Resilient Values of SDGs in the Indonesian Language Curriculum (CCS) - Roestamy, Martin; Martin, Abraham Yazdi; Rusli, Radif Khotamir; Humaira, Megan Asri; Suherman, Irman; Nita, Kamalasia Rio (Universitas Negeri Makassar, 2025)
This study aims to analyse the role of Compulsory Courses in the Indonesian Language Curriculum (CCS) in advancing the Sustainable Development Goals (SDGs) in Indonesia. Specifically, it investigates how CCS, as a foundational educational component, contributes to linguistic proficiency, character development, cultural preservation, and sustainable human progress, aligning with SDG targets such as quality education, economic growth, and environmental sustainability. The research employs a qualitative approach by analyzing national policies, pedagogical strategies, and recent academic literature related to Indonesian language education. This multi-faceted analysis evaluates the integration of SDG principles within CCS and assesses its effectiveness in fostering sustainable development. The findings reveal that CCS significantly strengthens national identity, academic literacy, and civic responsibility. It achieves this by embedding local wisdom, environmental consciousness, and social ethics into the curriculum. These outcomes occur because CCS serves as a holistic educational framework that not only emphasizes language skills but also integrates cultural and ethical values, thereby aligning with the broader objectives of the SDGs. The results of this study underscore the potential of CCS as a strategic tool for sustainable education in Indonesia. They provide a foundation for policymakers to refine and enhance the curriculum, ensuring it remains a robust platform for achieving long-term developmental goals. Furthermore, this research highlights the importance of integrating local and global perspectives in education to foster a more sustainable and equitable future.